"Allow access to location?": Digital feminist geographies. Issue 1 (2nd January 2016) - Tuzcu, Pinar
Abstract: This article looks at the impacts ongoing processes of digitization have on feminist politics of location. It argues that, rather than being borderless by nature, the digital has to be understood as producing different kinds of borders, demanding different kinds of politics of location. New potentialities arise with the challenge of creating a politics fitting to the current mode in which locations become slippery. Discussing the emergence of cyberfeminism in the early 1990s and a more recent example of digital feminism—the #SolitarityIsForWhiteWomen hashtag—this article thinks through the following questions: what does the "cyborg" as a posthuman (and postgender) category have to offer for those who have been (and are) excluded from the notion of the "human"? More specifically, how can we understand and conceptualize the "cyborg" beyond triumphalist narratives of being beyond difference?